A systematic review of the within-person association between physical activity and affect in children's and adolescents' daily lives. (January 2021) - Bourke, Matthew; Hilland, Toni A.; Craike, Melinda
Abstract: Background: It is important to understand the relationship between physical activity and affect because affect experienced during physical activity and momentary incidental affect may both predict physical activity behaviours. Additionally, affect experienced during physical activity may explain the mental health benefits of participation in physical activity. Utilising ambulatory assessment techniques, researchers can examine the acute within-person association between physical activity and affect in children and adolescents' daily life. The purpose of this study was to systematically review the literature to determine whether there is a within-person association between physical activity and affect in children and adolescents' daily life. Methods: Medline via EBSCOHost, SPORTdiscus, PsychINFO, and Scopus were searched up to March 2020. A narrative synthesis was used to summarize results of the included studies. Results: Ten studies, reporting on nine unique samples, met the inclusion criteria. The strongest evidence identified was for a positive within-person association between physical activity and subsequent positive affect and energy. The findings regarding the within-person association between physical activity and subsequent negative affect and moods were mixed, as were the findings regarding affect predicting subsequent physical activity. Conclusion: There was mixed support for the acute within-person association between physical activity and affect in children and adolescents. Future research should consider factors that may moderate the relationship between physical activity and affect. Additionally, experimental research should examine how manipulations of incidental affect effect physical activity participation in children and adolescents' daily life. Prospero Registration: CRD42020141649. Highlights: Consistent evidence of a positive association between physical activity and subsequent positive affect and energy. Less evidence regarding physical activity predicting subsequent negative affect and moods. Inconsistent evidence regarding affective states predicting subsequent physical activity.